STUDY ON EFFECT OF CABMV INFECTION ON THE CHANGES IN CHEMICAL COMPOSITION OF COWPEA CV. PUSA DOFASALI: Life Science-Botany - KUMAR YADAV, DR. RAJ; KUMAR, AVSHESH (International Journal of Life Science and Pharma Research, 2019)
The total nitrogen protein, nitrate nitrogen, nitrite nitrogen, and total free amino acids are higher in CABMV infected cowpea cv. Pusa Dofasali plant parts i.e. leaves, stems and roots than their healthy counterparts. However, the ammoniacal nitrogen was lower in infected plant parts than the healthy ones. The maximum amounts of total nitrogen, protein and total free amino acids was recorded in diseased leaves, nitrate nitrogen, and nitrite nitrogen in diseased roots and ammoniacal nitrogen in healthy leaves. The minimum amounts of total nitrogen, protein, nitrate nitrogen, nitrite nitrogen, ammoniacal nitrogen, and total free amino acids were present in the stem. Generally, nitrogenous fractions showed an increase up to 80th day of inoculation and afterwards, their concentration decreased. The concentration of total nitrogen, protein, nitrate nitrogen, nitrite nitrogen and total free amino acids was higher in diseased seed but ammoniacal nitrogen was higher in healthy seeds than diseased ones. An increased concentration of nitrogenous fraction in the virus infected plant parts of cowpea was observed. Unless previously fixed nitrogen was effectively used (or) transported elsewhere, the presence of excess nitrogenous compounds could alter the C/N ratio, which might inhibit the normal rate of nitrogen fixation. Virus infection usually brings about drastic changes in many physiological processes such changes were mainly studied with the vegetative parts of the host. Alteration due to virus infection in leguminous fruits received very little attention. Therefore, it was planned to study the effect of CABMV infection on the chemical composition of the cowpea cv. Pusa Dofasali fruits.